O ensino da disciplina de libras nos cursos de licenciatura em letras de uma instituição de ensino superior do estado de Pernambuco - Silva, Patricia Roberta da (2022)
The Brazilian Sign Language arrived at the university after being made official through Law 10.436/02, as well as Decree No. 5,626/2005, which instituted the discipline of Libras as mandatory in training courses in Speech Therapy, bachelor's and pedagogy, as well as optional for the other courses. Therefore, the general objective of this research emerges: To analyze the Libras discipline in the Degree Letters course of a Higher Education institution of the State of Pernambuco, seeking to understand the social importance of this discipline as a means of providing conscious inclusive educational practices, providing quality education and guaranteeing the right to access to education, which is exposed in the 1988 Constitution. Among the specific objectives, we sought: to understand how all historical and social evolution impacts the development of the deaf subject in society; Observe, from the professor's view of the Libras discipline, particular aspects that are present in the training course of teachers of Letters; Verify the social importance of this discipline in the Degree Letters course as a modifier of teaching practices; Prepare a manual with proposals of some relevant activities that can be applied in the Libras discipline. We conducted a survey of productions of other authors that address the theme, observing their conclusions. Thus, on the theoretical basis of this research, there are questions about mother tongue, according to LEITE (1995); the conception of second language, according to Muñoz & Ceia (2011); bilingualism, according to Quadros (2004); deaf education, according to Goldfeld (2021), Skliar; Massone; Veinberg (1995) and Strobel (2018); the teaching of Libras, according to Gesser (2012); and teacher education, according to Freire (1996), Nóvoa (1992), among others. We conducted a survey of productions of other authors that address the theme, observing their conclusions. Thus, on the theoretical basis of this research, there are questions about mother tongue, according to LEITE (1995); the conception of second language, according to Muñoz & Ceia (2011); bilingualism, according to Tables (2004); deaf education, according to Goldfeld (2021), Skliar; Massone; Veinberg (1995) and Strobel (2018); the teaching of Libras, according to Gesser (2012); and teacher education, according to Freire (1996), Nóvoa (1992), among others. The methodology used was qualitative and quantitative, through a bibliographic and documentary research, composed of a semi-structured interview with the professors who teach the discipline of Libras in the Degree Letters course of a public university in the State of Pernambuco. As a result, the research showed that the discipline of Libras has an insufficient workload in view of the great demand to offer subsidies to future Portuguese-speaking teachers, in order to build their praxis aware of the singularities and needs of deaf students included in the classroom, providing a reflexive teaching, in search of a quality education for all.